Nesting of groups: Links among personal magnetism, community trust, inequality perception and depression - Peicheng Wang; Yujie Zhang (PLoS ONE, 2025)
Background In the context of China’s rapid transition from a collectivist work-unit system to a more individualized, community-oriented society, this study investigates the relationship between personal magnetism—an individual’s social appeal—and its protective role in mitigating depression. Objective This study aims to examine the moderating role of perceived inequality and the mediating effect of community trust in the relationship between personal magnetism and depression. Methods Utilizing longitudinal data from the China Family Panel Studies (CFPS) from 2018 to 2020, involving 26,711 respondents aged 16 to 96, this study employs multivariate regression models to explore these relationships. Results The findings reveal that perceived inequality amplifies the negative relationship between personal magnetism and depression, suggesting that personal magnetism becomes less effective in alleviating depressive symptoms in contexts of higher inequality. Additionally, community trust is identified as a key mediator, explaining how strong social networks can buffer the psychological effects of inequality and enhance mental well-being. Conclusion The findings underscore the importance of fostering community trust and addressing income inequality in public policy. By leveraging the positive effects of personal magnetism and social solidarity, targeted interventions can reduce depression and enhance collective well-being in societies undergoing socio-economic transformation.